JUMLAH ION KROMIUM (Cr) DAN NIKEL (Ni) KAWAT ORTODONTIK STAINLESS STEEL YANG TERLEPAS DALAM PERENDAMAN SALIVA - Jura, Ciendy O.; Tendean, Lydia E. N.; Anindita, P. S. (Universitas Sam Ratulangi, 2015)
Abstract: Orthodontic stainless steel wire is one of the instrument components oftenly used in orthodontic treatment and may persist in the oral cavity for a long period of time. Orthodontic stainless steelwire in the oral cavity can be corrosive in the presence of Cr and Ni ion release which can be harmful to the human body and the stainless steel wire itself. This study aimed to determine the amount of Cr and Ni ions released from the stainless steel orthodontic wire that was immersed in artificial saliva. This was an experimental laboratory study with a posttest only control group design. Samples were analyzed by using a UV-Vis spectrophotometry to determine the released Cr and Ni ions in the saliva. Samples consisted of 4 brands of orthodontic stainless steel wires immersed in artificial saliva for 30 days with a temperature of 370C. Data were analyzed by using a computer program. The results showed that the release of Cr ions in samples A, B, C, and D respectively were: 0.302 ppm, 0.331ppm, 0,311 ppm, and 0.483 ppm meanwhile of Ni ions were 1.930 ppm, 1.778 ppm, 1.654 ppm, and 1.391ppm. Conclusion: The release of Cr and Ni ions varied in each sample of orthodontic stainless steel wire .Keywords: orthodontic stainless steel, Cr, Ni, artificial saliva, UV-Vis spectrophotometryAbstrak: Kawat ortodontik stainless steel merupakan salah satu komponen alat yang sering digunakan dalam perawatan ortodontik dan dapat bertahan dalam rongga mulut untuk jangka waktu yang lama. Kawat ortodontik stainless steel yang berada di dalam rongga mulut dapat mengalami korosi dengan adanya pelepasan ion Cr dan Ni yang bersifat merugikan bagi tubuh manusia dan kawat ortodontik itu sendiri. Penelitian ini bertujuan untuk mengetahui besarnya jumlah pelepasan ion Cr dan Ni dari kawat ortodontik stainless steel yang direndam dalam saliva buatan. Penelitian ini menggunakan metode eksperimental laboratorium dengan rancangan posttest only control group. Sampel diuji dengan menggunakan spektrofotometri UV-Vis untuk mengetahui pelepasan ion Cr dan Ni dalam saliva. Sampel terdiri dari 4 merek kawat ortodontik stainless steel direndam dalam saliva buatan selama 30 hari dengan suhu 370C. Data hasil penelitian dianalisis menggunakan program komputer. Hasil penelitian menunjukkan pelepasan ion Cr pada sampel A, B, C, dan D berturut-turut 0,302 ppm; 0,331 ppm; 0,311 ppm; dan 0,483 ppm sedangkan pelepasan ion Ni 1,930 ppm; 1,778 ppm; 1,654 ppm; dan 1,391 ppm. Simpulan: Pelepasan ion Cr dan Ni bervariasi dari masing-masing sampel kawat ortodontik stainless steel.Kata kunci : Kawat ortodontik stainless steel, Cr, Ni, saliva buatan, spektrofotometri UV-Vis